Comparison of patient referral processes between rural and urban health facilities in Liberia - J. Kim*; C. Babcock; M. Barreix; C. Bills (African Journal of Emergency Medicine, 2013)
Since the 2003 peace talks, the Liberian government has made progress in rebuilding a comprehensive national health system. However, the effective referral of patients from one health facility to another remains a challenge, especially in rural areas. The objective of this study is to compare referral care practices at rural and urban health facilities in the most populous county in Liberia. Methods: A cross-sectional health referral survey was conducted at a representative sample of primary clinics, health centres and hospitals in Montserrado County, Liberia. The survey was administered via direct interview with a qualified director of each health facility by a single observer. The survey describes baseline facility data, characteristics of referrals, referral guidelines used, transport modes and communication methods. Referral processes were compared between rural and urban health facilities. Results: During the 6-week study, 62 health facilities were surveyed. Most facilities were considered urban (n = 52, 84%). Average patient presentations to rural outpatient and inpatient health facilities during the 3-months prior to the study period was 3182.8 and 42.4, respectively, compared to 2559.0 and 866.8 at urban outpatient and inpatient facilities. The mean percent of referred patients at rural health facilities was 51.8% compared to 10.7% at urban facilities (p = 0.004). The mean overall distance to the referred health facility (p = 0.025), and cost of taxi transfer was greater among rural health facilities (p = 0.093). Conclusions: Patient referral systems in Liberia are relatively unsystematic. While formal and informal mechanisms for referrals exist at both rural and urban health facilities, establishing guidelines for referral care practices and transportation strategies tailored to each of these settings will help to strengthen the healthcare system as a whole.